A qualitative investigation of school age children, their parents and school staff on their participation in the Digital Education to LImit Salt in the Home (DELISH) program. Issue 4 (6th July 2020) - Bouterakos, M; Booth, A; Khokhar, D; West, M; Margerison, C; Campbell, K J; Nowson, C A; Grimes, C A
Abstract: This study explored the views of participants who completed a 5-week, online, interactive, family-based, salt reduction education program (Digital Education to LImit Salt in the Home). A secondary aim was to explore the views of school staff on the delivery of food and nutrition education in schools. Children aged 7–10 years, their parents and principals/teachers from participating schools located in Victoria, Australia, completed a semi-structured evaluation interview. Audio-recordings of interviews were transcribed verbatim and analysed using NVivo. Twenty-eight interviews (13 children; 11 parents; 4 school staff) were included. Thematic analysis revealed that the program was well received by all groups. Children reported that the interactivity of the education sessions helped them to learn. Parents thought the program was interesting and important, and reported learning skills to reduce salt in the family diet. School staff supported the delivery of nutrition education in schools but indicated difficulties in sourcing well-packed nutrition resources aligned with the curriculum. It appears that there is support from parents and teachers in the delivery of innovative, engaging, nutrition education in schools, however such programs need to be of high quality, aligned with the school curriculum and readily available for incorporation within the school's teaching program.